Avaliação de um sistema de gestão de desempenho: a percepção dos funcionários do Banco Itaú - Cruz, Marcello Cipola (2008)
This research is conducted within the field of human resource management and organizational behavior. The purpose of the research is to evaluate the performance management system from a Brazilian company from its workers perceptions. Specifically, the study aims to understand the perception of the impact of management performance to the success of the organization and for the professional development. From a qualitative approach, twelve interviews were conducted with employees from Banco Itaú. Results were interpreted according to one specific technique of content analysis: the thematic categorical analysis. The main findings in the study were: (i) the categories that compose the performance management in the company are: result-orientation, performance appraisal, peopleorientation, the 'tool' and professional development, and there are other categories that influence the performance management: the manager’s role, the spectator attitude, the operational heterogeneity and culture; (ii) from the employees’ perspective, performance management practiced in the company does not help the professional development and consequently, it is not effective for the company; (iii) the manager’s role is crucial for the employees’ perception about performance management.